Adaptive Subcarrier Allocation for MIMO-OFDMA Wireless Systems Based on Beamforming - 管张均 张唯炯 周希朗 郭强 (Dong Hua da xue xue bao. Zi ran ke xue ban., 2010)
Beamforming is a kind of signal processing technique which can improve system performance in the multiple-input multiple-output（MIMO）systems.In this paper,the problem of allocating subcarriers in MIMO-OFDMA wireless systems was analyzed,and a scheme to allocate subcarriers among all users based on beamforming was proposed to maximize the signal-to-noise ratio（SNR）at the receiver.Statistical properties of the channel matrix were studied,and some beneficial results were got.Statistical channel state information（CSI）was also taken into account to simulate more practical systems.Simulation results show that the proposed allocating scheme is effective,and it is robust to the influence of delayed CSI.